Millainen kirjoittaja olen? Kielten yliopisto-opiskelijoiden näkemyksiä kirjoittajuudesta - Laine, Päivi; Mutta, Maarit (Suomen Soveltavan Kielitieteen Yhdistys AFinLA ry, 2026)
The article explores 131 university students’ self-perceptions as multilingual writers. Data was gathered from Master’s level language students (2021–2024), who wrote reflective descriptions of themselves as writers freely but with the help of guiding questions. Reflective writing was used to help students articulate their beliefs about writing and writer agency. NVivo was employed to analyse the data and create thematic categories that emerged from it. Findings indicate that language students are experienced writers, often writing in languages other than Finnish. The writer agency of many participants is linked to the identity they have developed at school. Students’ writing routines vary, and many still consider handwriting as a creative way of expressing themselves. The choice of writing device varies depending on the writer. Moreover, for some students, English often replaces Finnish as their primary writing language in their everyday life, influenced by academic demands and leisure activities.
AFinLAn vuosikirja 2025: Kieli avaimena muuttuvaan maailmaan